BODIPY‐based Carbonaceous Materials for High Performance Electrical Capacitive Energy Storage. Issue 20 (19th September 2018) - Wang, De‐Gao; Wang, Huan; Song, Min; Yu, Guipeng; Kuang, Gui‐Chao
Abstract: Incorporation of heteroatoms into carbon materials is crucial to tailor carbon materials' donor‐acceptor properties and consequently tune their chemical and electrical performance. However, doping carbon materials with multi‐heteroatoms (three or more, especially the light elements) has been rarely payed attention until now. In this work, we develop a porous organic polymer containing boron, nitrogen, fluorine elements and realize its corresponding carbonaceous materials by subsequent carbonation or KOH activation process. Electrochemical measurements results reveal that KOH activation sample (BPOP‐700A ) is endowed with excellent specific capacitance of 408 F g −1 in three‐electrode system and an energy density over 19.2 Wh kg −1 in two‐electrode system at aqueous electrolyte, which can be attributed to multi light elements (boron, nitrogen and trace fluorine) doping, favorable morphology and rational pore size distribution architecture. In addition, BPOP‐700A displays well rate ability and outstanding cycle performance (10 A g −1, 10 000 cycles, 95 % retention). Our work might give some hints in designing multi light element doping carbon materials in supercapacitor applications. Abstract : Amorphous materials : Carbonaceous materials (BDP‐700A ) containing boron, nitrogen and fluorine groups and a porous organic polymer delivered impressive electrochemical properties with a specific capacitance of 408 F g −1 in a three‐electrode system and an energy density over 19.2 Wh kg −1 in a two‐electrode system in an aqueous electrolyte.